Post-operative pain and associated factors after cesarean section at Hawassa University Comprehensive Specialized Hospital, Hawassa, Ethiopia: A cross-sectional study. (September 2022) - Hussen, Ibrahim; Worku, Misganaw; Geleta, Dereje; Mahamed, Abbas Ahmed; Abebe, Mesfin; Molla, Wondwosen; Wudneh, Aregahegn; Temesgen, Tasfaye; Figa, Zerihun; Tadesse, Muhiddin
Abstract: Background: The most frequent obstetric surgery both in Ethiopia and around the world is the cesarean section (CS). Postoperative pain that is not well managed can have a major negative impact on surgical patient morbidity, delaying healing and the return to normal daily activities. Even though the cesarean section is one of the most commonly performed operations, postoperative pain after cesarean section and associated factors has not been studied. Objective: To assess the magnitude and factors associated with postoperative pain after cesarean section at Hawassa University Comprehensive Specialized Hospital, Hawassa, Ethiopia. Methods: From February 1 to September 30 in 2021, a hospital-based cross-sectional study was undertaken among women who underwent cesarean deliveries at Hawassa University Comprehensive Specialized Hospital. The patient's medical file was read, and information was gathered from them using a structured questionnaire and checklist. The information was prepared for analysis by being cleaned, coded, and put into EPI Data version 3.1 before being exported to SPSS version 20. The prevalence rate and socio-demographic details were displayed using descriptive statistics. Bivariate and multivariable logistic regression analysis was done to identify the associated factors. Variables with a p-value of <0.05 were considered statistically significant. Results: The magnitude of moderate to severe post-operative pain after a cesarean section was 89.8% (95% CI 84.7, 93.5). Duration of procedure (AOR: 3.62, 95% CI: 1.33, 15.85), type of anesthesia (AOR: 2.38, 95% CI: 1.31, 8.71), and type of analgesics administered (AOR: 2.3, 95% CI: 1.28, 19.21) were significantly associated with moderate to severe post-operative pain. Conclusion: In this study a significant number of parturient in this study reported moderate to severe post-cesarean pain within 24 h. The duration of the procedure, the type of anesthesia used, and the type of analgesics administered were all found to be significantly associated with postoperative pain after cesarean section. Highlights: The magnitude of post-operative pain after a caesarean section was 89.8%. About 84.2% reported moderate to severe pain at 24 h after surgery. Duration of procedure was significantly associated to postoperative pain. Anesthesia type used was found to be significantly associated to postoperative pain.